2016
DOI: 10.1523/jneurosci.0621-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Ulk4 Is Essential for Ciliogenesis and CSF Flow

Abstract: Ciliopathies are an emerging class of devastating disorders with pleiotropic symptoms affecting both the central and peripheral systems and commonly associated with hydrocephalus. Even though ciliary components and three master transcriptional regulators have been identified, little is known about the signaling molecules involved. We previously identified a novel gene, Unc51-like-kinase 4 (ULK4), as a risk factor of neurodevelopmental disorders. Here we took multidisciplinary approaches and uncovered essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
68
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(75 citation statements)
references
References 50 publications
7
68
0
Order By: Relevance
“…These patients manifested heterogeneous clinical symptoms, including developmental delay, behavioral problems, severe learning difficulties, severe language delay, speech delay, and others ( Table 1 ). Recently, it has been reported that ULK4 regulates the FOXJ1 pathway and an array of other molecules involved in ciliogenesis [Liu et al, 2016b].…”
Section: Discussionmentioning
confidence: 99%
“…These patients manifested heterogeneous clinical symptoms, including developmental delay, behavioral problems, severe learning difficulties, severe language delay, speech delay, and others ( Table 1 ). Recently, it has been reported that ULK4 regulates the FOXJ1 pathway and an array of other molecules involved in ciliogenesis [Liu et al, 2016b].…”
Section: Discussionmentioning
confidence: 99%
“…They belong to ULK families already implicated in flagellum-related functions in animals (35,36) with the mammalian ULK Fused demonstrated to be essential for construction of motile cilia (35). Plant orthologs of both kinases were shown to be critical for the phragmoplast organization, resembling the function of plant kinesin-15s (37,38).…”
Section: The Fc Is a Membrane Junction Attached By Two Types Of Kinesmentioning
confidence: 99%
“…Two proteins that are homologous to geminin-Mcidas and GemC1-promote the expression of the Foxj1 and c-Myb transcription factors, all of which are necessary for ependymal cell differentiation (Malaterre et al 2008;Jacquet et al 2009;Stubbs et al 2012;Tan et al 2013;Kyrousi et al 2015). The transcription factors Trp73 (Yang et al 2000;GonzalezCano et al 2016), Yap (Park et al 2016), and Gli3 (Wang et al 2014) and the kinase Ulk4 (Liu and Guan 2016) are also required for ependymal cell differentiation. There are also many genes that, when mutated, impair cilia function and can contribute to the development of hydrocephalus (Fliegauf et al 2007;Tissir et al 2010;Ohata et al 2014).…”
mentioning
confidence: 99%